Resilience of the genus Agaricus to climatic variability in and around Ayubia National Park, Pakistan - Ali, Mohammad; Nasim, Ghazala (Mushroom Research, 2016)
The environment is being altered very quickly with the passage of time. No doubt human activities have a main role in the enhancement of certain environmental issues and these problems are affecting the natural biomes and the ecosystem world over. The biodiversity has to face these cascading problems and have to compete for their natural habitat. These environmental threats have pushed unique biodiversity at the edge of the extinction. The present study was focused to examine these issues for the members of genus Agaricus.Â